The role of executive functions and psychiatric symptom severity in the Allen Cognitive Levels. (January 2018) - Schubmehl, Sarah; Barkin, Samuel H.; Cort, Doug
Abstract: This study examined the relationship between Allen Cognitive Level (ACL) and psychiatric symptom severity, level of nursing support required to complete activities of daily living (ADLs), and post-hospitalization discharge disposition in a sample of 193 acute psychiatric inpatients. A subsample of 31 participants with acute psychotic disorders were administered three measures of executive functioning in order to examine the convergent validity between ACL and basic sequencing and shifting, phonemic fluency, and visuospatial construction. Findings indicated significant moderate positive correlations between ACL and motor processing speed, basic sequencing and shifting, and phonemic fluency, and a nonsignificant relationship with visuospatial construction. A subsample of 166 participants were administered the Brief Psychiatric Rating Scale-Expanded (BPRS-E) to assess psychiatric symptom severity. Results indicated a significant weak negative correlation between ACL and total psychiatric symptomatology, as well as significant weak negative correlations with specific symptoms. In contrast with prior research, there was no significant correlation between ACL and level of nursing assistance required to complete ADLs. A logistic regression did not identify ACL as a contributing factor to post-hospitalization discharge disposition. These findings call into question the clinical utility of the ACLS-5 as an assessment of functional cognition for those experiencing acute psychiatric illness. Highlights: Convergent validity of ACLS-5 with measures of phonemic fluency and basic sequencing and shifting. Psychiatric symptom severity can influence ACL performance. ACL poor predictor of post-hospitalization discharge disposition. No significant relationship between level of nursing assistance with ADLs and ACL.